Etika Pelayanan dalam Pendidikan Islam: Membangun Budaya Pelayanan Berbasis Nilai-Nilai Islami - Melly Ersanda; Amalia Rahmah; Rasti Pramudita (JOURNAL SAINS STUDENT RESEARCH, 2026)
Service is a crucial aspect of education. From an Islamic perspective, service is not only oriented towards customer satisfaction but also an integral part of worship and the implementation of noble moral values. This article discusses the concept of service ethics in Islamic education, the Islamic values ​​that underlie it, and the importance of building a service culture oriented towards professionalism, honesty, responsibility, and mutual respect. By implementing good service ethics, Islamic educational institutions are expected to improve the quality of their services and foster a harmonious and character-based educational environment.